Web-Based Student Learning Activities and Development Information System Using Pieces Analysis at OSI Tutoring Center - Septiani, Anugrah; Heni Rahmawati; Luthfi Nur Azizah (CV.RIZANIA MEDIA PRATAMA, 2025)
Tutoring (BIMBEL) is a form of non-formal education that plays a role in improving students' academic achievements. Oemah Sinau Indonesia (OSI) in Banjarnegara still uses Excel and physical reports to record learning activities and student development, making the process of searching and distributing data less efficient. This study aims to build a web-based information system for learning activities and student development using the PIECES analysis as a system evaluation method at OSI tutoring. The system development uses the Waterfall method with PHP programming language, Laravel framework, and data storage based on Firebase Realtime Database. System testing is conducted using Black-box testing to ensure the system functions according to user needs, and all 10 test scenarios were successfully executed with a